Northern gannets in central Portugal: diet and marine litter assessment - Hadden, Ana Carolina Amador (2021)
Seabirds occur in a great variety of marine ecosystems worldwide, being exposed to many anthropogenic threats such as fisheries bycatch and several types of pollution. Interactions of these seabirds with fishing gear and marine litter may lead to harmful or even deadly outcomes, such as plastic ingestion or injury and death by entanglement. Northern gannets are among the most widespread seabirds in continental waters during wintering and migratory periods. Along the Iberian coast, this species is present predominantly between late July and early December, leading to larger numbers of individuals in Portuguese marine animal rehabilitation facilities during this period. Several reports suggest that gannets seem to be not only one of the most accidentally bycaught species along the Portuguese coast, but they are also prone to ingestion of marine debris due to their foraging method. In order to better understand this species’ interactions with fisheries and to acquire more information on its main prey, the gastrointestinal contents of northern gannets found stranded in the central/north Portuguese coast were analysed. The level of ingested plastics was also characterized. A short analysis of Northern Gannet diet was obtained, in which it was possible to identify Trisopterus spp., Ommastrephes spp. and Loligo spp.. Gannets ingested both micro and macroplastic items, although microplastics were the most frequently found items. Fibres and fragments were the most prevalent items although fishing hooks, fishing lines and user plastics, were also detected. More studies into the Northern Gannet's potential role as a marine litter monitoring tool in wintering areas are needed. It is extremely important to continue quantifying and investigating the interactions (whether ingestion or entanglement) of marine species with plastics and fishing-related gear.